2013
DOI: 10.2337/db12-1819
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Labeling and Imaging of Insulin Secretory Granules

Abstract: Insulin is stored within the secretory granules of pancreatic β-cells, and impairment of its release is the hallmark of type 2 diabetes. Preferential exocytosis of newly synthesized insulin suggests that granule aging is a key factor influencing insulin secretion. Here, we illustrate a technology that enables the study of granule aging in insulinoma cells and β-cells of knock-in mice through the conditional and unequivocal labeling of insulin fused to the SNAP tag. This approach, which overcomes the limits enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 34 publications
6
85
1
Order By: Relevance
“…1A and Movie S1). These time intervals were close to those applied in previous studies on insulin turnover (31,37). Our initial analyses indicated that young and old SGs did not significantly differ in regards to their collective diffusion coefficient (Fig.…”
Section: Significancesupporting
confidence: 90%
See 2 more Smart Citations
“…1A and Movie S1). These time intervals were close to those applied in previous studies on insulin turnover (31,37). Our initial analyses indicated that young and old SGs did not significantly differ in regards to their collective diffusion coefficient (Fig.…”
Section: Significancesupporting
confidence: 90%
“…The availability of cell-permeable nonfluorescent and fluorescent SNAP substrates, such as TMR-Star, allows for a broad variety of applications. Ins-SNAP labeled with TMRStar (Ins-SNAP TMR-Star ) is properly sorted into SGs and secreted upon glucose stimulation (31). Importantly, high-content image analyses formally demonstrated that the preferential release of young Ins-SNAP TMR-Star+ SGs is a homogenous response to stimulation rather than being primarily sustained by a more biosynthetically and secretory active subpopulation of cells.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that newly formed SGs are especially favored for recruitment into the readily releasable vesicle pool (40)(41)(42)(43)(44). Thus, a defect in the biogenesis of new SGs should result in a limited pool of these new vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…When the granules are younger (approximately 12-18 hours) they appear green, and after 24-36 hours the granules are red, and thus the reporter serves as a live cell timer that enabled us to distinguish new versus old SGs. It is well documented that in insulin-secreting cells, there is preferential release of newly formed granules in response to a stimulus (40)(41)(42)(43)(44), which predicts that we should see selective depletion of green granules.…”
Section: Ectopic Expression Of the Sorcs1 Luminal Domain Phenocopies mentioning
confidence: 99%